Cumulative risk disparities in children's neurocognitive functioning: a developmental cascade model. Issue 2 (6th April 2015) - Wade, Mark; Browne, Dillon T.; Plamondon, Andre; Daniel, Ella; Jenkins, Jennifer M.
Abstract: The current longitudinal study examined the role of cumulative social risk on children's theory of mind (ToM) and executive functioning (EF) across early development. Further, we also tested a cascade model of development in which children's social cognition at 18 months was hypothesized to predict ToM and EF at age 4.5 through intermediary language skills at age 3. We then examined whether this developmental mechanism varied as a function of social risk status. Participants were 501 children recruited when they were newborns, at which point eight psychosocial risk factors were assessed and combined into a metric of cumulative social disadvantage. Families were followed up at 18 months, at which point four social‐cognitive skills were assessed using developmentally sensitive tasks: joint attention, empathy, cooperation, and self‐recognition. Language was measured at age 3 using a standardized measure of receptive vocabulary. At age 3 and 4.5, EF and ToM were measured using previously validated tasks. Results showed that there were notable cumulative risk disparities in overall neurocognitive skill development, and these effects became more differentiated over time. Support was also found for a developmental mechanism wherein the effect of social cognition at 18 months on ToM and EF in the preschool period operated specifically through children's receptive language ability at age 3. This pathway functioned similarly for children with both low‐ and high‐risk backgrounds. These results extend previous findings by documenting the role of cumulative social disadvantage on children's neurocognition and the pathways that link key neurocognitive abilities across early development. Abstract : This study shows that social cognition at 18 months is associated with children's theory of mind and executive functioning at age 4.5, and that these effects operate through their language skills at age 3. This mechanism operates similarly for children from both low and high cumulative risk backgrounds. However, high‐risk children show lower overall neurocognitive skill development, suggesting that early identification and intervention is important to mitigate the negative downstream consequences of neurocognitive morbidity.